Challenges and opportunities in the Nigerian economy - A National Institute Publication; Mailafiya, Obed.; National Institute for Policy and Strategic Studies (Nigeria) (Kuru [Nigeria] : National Institute for Policy and Strategic Studies, 1989)
This book provides a more effective ways to fight unemployment and to assist unemployed youths to key in to other opportunities in the private sectors including self employed enterprises.
Results of a workshop held in the National Institute for Policy and Strategic Studies, Kuru, Nigeria, Dec. 1988.
Includes bibliographical references.
asm; 21/01/19
Loans
Keywords: New business enterprises; Industries; Nigeria; Nigeria